Teachers' Strategies to Encourage Students' Participation in English Classroom - Putri, Syalwa Annisa; Salam, Urai; Rezeki, Yanti Sri (English Education:Journal of English Teaching and Research, 2024)
Teachers have an important role in creating a supportive environment in English lessons and should encourage students to participate actively. Appropriate teaching strategies can be employed to encourage student participation in the English classroom. This study was conducted to investigate strategies used by the teachers to encourage students’ participation in the English classroom at SMPN 01 Sungai Raya. The researcher employed a case study methodology, utilizing observation, interview, and document analysis as data collection methods to identify the strategy used by English teachers to encourage student participation. Based on the findings from observation, interview, and document analysis, it can be concluded that English teachers employed various strategies to encourage student participation in the classroom, such as questioning strategy, collaborative learning, motivational learning, and differentiation learning.